Enhanced C–F Activation and Proton Supply over Al2O3-Embedded RuO x Clusters Boost Perfluorocarbon Hydrolysis - Lupeng Han; Jing Gao; Chaoqi Zhang; Haotian Huang; Yuan Wang; Wenqiang Qu; Jingwei Hou; Gloria Berlier; Emiliano Cortés; Dengsong Zhang (Journal of the American Chemical Society, 2026)
Abstract The catalytic hydrolysis of per- and polyfluoroalkyl substances (PFAS) holds significant potential for environmental remediation; however, the chemically inert C–F bond poses substantial challenges for achieving efficient low-temperature activity. Herein, we demonstrate that RuOx clusters embedded in mesoporous Al2O3 nanosheet (RuOx/Al2O3) catalysts achieved the complete decomposition of CF4, one of the most chemically inert PFAS, at an unprecedented low temperature of 450 °C, outperforming all catalysts reported to date. The extraordinary CF4 hydrolysis performance is attributed to synergistically enhanced C–F bond activation and proton supply. Specifically, the strong electronic interaction between RuOx clusters and Al2O3 promotes the CF4 adsorption and C–F cleavage on Al sites in RuOx/Al2O3. Furthermore, the Ru sites in RuOx/Al2O3 promote H2O dissociation into *H and *OH, which enables the continuous regeneration of adjacent Al–OH groups and supplies sufficient protons for defluorination in the CF4 hydrolysis reaction. This study paves the way for designing and developing highly efficient catalysts for low-temperature catalytic hydrolysis of PFAS.